Effects of Alcohol Extracts From Ganoderma resinaceum on Sleep in Mice Using Combined Transcriptome and Metabolome Analysis - Chen, Tianci; Zhang, Fangyi; Chen, Juanqin; Zhong, Qiangui; Hu, Yuxin; Wu, Ruru; Xie, Baogui; Jiang, Yuji; Chen, Bingzhi (Frontiers in Nutrition, 2022)
Abstract: Ganoderma resinaceum is a valuable Chinese medicine. This study aimed to investigate whether a G. resinaceum alcohol extract (GRAE) improves sleep, and analyze the potential mechanism. After 30 days of continuous administration of GRAE at various doses, GRAE (1000 mg/kg.bw) prolonged pentobarbital sodium-induced sleep, increased the rate of sleeping in mice treated with a subthreshold dose of pentobarbital sodium, and shortened sleep latency. The mice brain was analyzed using UPLC-MS/MS and RNA-sequencing. Metabolomics analysis revealed that 73 metabolites in the high-dose (HD) group had changed significantly, mainly in amino acids and their derivatives, especially the accumulation of L-glutamine and PGJ2 (11-oxo-15S-hydroxy-prosta-5Z, 9, 13E-trien-1-oic acid). Transcriptome analysis revealed 500 differential genes between HD and control groups, mainly enriched in neuroactive ligand-receptor interaction, amphetamine addiction, and cocaine addiction pathways. The conjoint analysis of the transcriptome and metabolome showed that the biosynthesis of L-glutamine might be regulated by Homer1, Homer3, and Grin3b. This suggests that GRAE may affect L-glutamine accumulation by regulating the expression of these genes. This study showed that GRAE may prolong the sleep time of mice by reducing the accumulation of L-glutamine and deepens our understanding of the regulatory network between certain genes and L-glutamine.